Necesidad de reformar el artículo 226 del código civil, incorporando un literal que garantice el principio superior del niño al momento de dar por terminado la unión de hecho - Yanza Infante, Vanessa Estefania (2015)
The Constitution of 2008 the union in Article 68 states "The stable and monogamous union between two people free of marriage to form a de facto household for the period and the conditions and circumstances that the law was ratified generate the same rights and obligations as those of families constituted through marriage. " I think there are still legal loopholes regarding this issue, upon completion of the union, because it is causing serious damages to couples who have decided to unite their lives through this legal union of fact and then having lived some time, one of the two people decide to voluntarily end this relationship, leaving his partner and children under age of total helplessness, causing serious economic, psychological and social damage; therefore this issue should be considered in several legal analysis and thus able to suggest alternative solutions to guarantee that the higher principle of the child when it is terminated law marriage is respected. For the foregoing reasons, I am in dire need of conceptualizing, framing, describe and analyze this phenomenon of transcendental importance within the various aspects and contexts, in order to objectively evaluate the resources that are counted and thus present a concrete proposal to allow legal remedy deficiencies that could be found in the present study Code regarding the termination of the union in Ecuador.